The Produced Self: Conflicts of Depersonalization in Edith Wharton’s The House of Mirth - Blanco Hidalga, Jesús (Complutense Journal of English Studies, 2019)
American critic Fredric Jameson has referred to the modern centred subject as a consequence of the historical development of capitalism: both a product of and compensation for the processes of reification and fragmentation brought about by our mode of production. For the critic, realism and modernism played a fundamental part in the consolidation of modern individuality through the use of textual strategies such as point of view and free indirect discourse, which conjure up the literary illusion of a unified self. These are procedures deftly used by Edith Wharton to build our novel’s central character, Lily Bart. At the same time, however, this individuality is inevitably threatened by Wharton’s particular views of society, influenced by social Darwinism, and by her acute awareness of social processes of reification and commodification. This article explores the conflict between Wharton’s proposal of a unified self and the reality of depersonalization reflected by the novel. Likewise, this essay examines the strategies of containment through which the novelist seeks to assuage this contradiction and compensate for the almost unbearable loss that her social views entail for the subject.